Kinerja Birokrasi Pelayanan Administrasi Kurikulum pada Unit Pelaksana Teknis (UPT) SMP Negeri 6 Medan - Aruan, Imelda Fransisca; Siregar, Nina Siti Salmaniah; Hartono, Budi (Mahesa Research Center, 2023)
Based on the results of discussions and interviews conducted by researchers at UPT SMP Negeri 6 Medan, the problem that needs to be addressed is the teachers who feel underserved by the curriculum administration staff. Among them there are still delays in curriculum administration services needed by teachers, namely delays in issuing decrees for the distribution of teaching tasks, delays in issuing additional teaching assignments and also delays in providing complete documents supporting learning tools for teaching and learning activities. The author uses a descriptive method that leads to qualitative research that aims to examine the quality problems of the performance of the curriculum administration service bureaucracy at UPT SMP Negeri 6 Medan. Data collection techniques used in this research are documentation and interview techniques. The data analysis used by the researcher in this research is qualitative analysis. From the results of research conducted by researchers that the performance of the curriculum administration service bureaucracy at UPT SMP Negeri 6 Medan is good but still needs to be addressed and improved to be even better in the future, especially in the current era. Government regulations regarding curriculum administration services are contained in the Regulation of the Minister of National Education of the Republic of Indonesia Number 24 of 2008 concerning Standards for School/Madrasah Administrative Personnel.